INTERFERON GAMMA AND INTERLEUKIN-10 LEVELS IN PBMC OF ACTIVE AND LATENT TUBERCULOSIS PATIENTS AS WELL AS HEALTHY INDIVIDUALS - Tedja, I G.A. Wiradari; Tambunan, Betty Agustina; Oetami, Fransisca Sri; Nugraha, Jusak (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Tuberculosis (TB), an infectious disease caused by a Mycobacterium tuberculosis, is still a health problem in Indonesia, and the world. One of the failures to control the TB epidemic is due to the lack of effective vaccines available today. Protective immune responses to M.tuberculosis are dominated by cellular immunity and less by humoral immunity. IFN-γ, and IL-10 play a role in the protection of against M.tuberculosis, and the pathogenesis of TB. Fusion antigen ESAT-6-CFP-10 has a strong antigenicity to T cells and stimulates specific cellular immune responses, thereby providing benefit in immune responses that are protective against M.tuberculosis infection. The aimed of this study was to know the difference betwen IFN-γ, and IL-10 levels on PBMC culture of active TB, latent TB, and healthy people after ESAT-6-CFP-10 fusion antigen stimulation. This study used an in vitro of quasi experimental design in PBMC cultures of active TB, latent TB, and healthy people groups stimulated by ESAT-6-CFP-10 antigen fusion Mycobacterium tuberculosis. IFN-γ, and IL-10 levels were measured by ELISA method. The results were analyzed by one-way ANOVA. The mean levels of IFN-γ post-stimulation of ESAT-6-CFP-10 fusion antigens did not differ (p=0.359) in the active pulmonary TB group (0.07 - 2114), latent TB (6.84 - 1381) and healthy people 1.88 - 1807.70), as well as the mean levels of IL-10 (p=0.712) in the active pulmonary TB (16.70 - 328.80), latent TB (29.70 - 323.60 ) and healthy people (31.30 - 958). There were no significant differences in levels of IFN-γ and IL-10 in active TB, latent TB, and healthy people after stimulation by fusion antigen ESAT-6-CFP-10.